HUBUNGAN MEDIA SOSIAL DAN GAME ONLINE DENGAN PERILAKU BELAJAR PADA MATA PELAJARAN AKIDAH AKHLAK SISWA DI MADRASAH ALIYAH NEGERI 3 KOTA JAMBI - Irliadurrah, Marshanda Putri; Risnita; Darma Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the relationship between social media and online gameuse and student learning behavior in the Aqidah Akhlak (Islamic Creed) subject atMAN 3 Jambi City. The study used a quantitative approach with correlationalmethods. The sample consisted of 251 students selected using proportionaterandom sampling. Data were collected through a questionnaire based onindicators for each variable and analyzed using product-moment correlation andmultiple correlation. The results showed a positive and significant relationshipbetween social media use and learning behavior (R = 0.4445; KD = 19.75%) andbetween online games and learning behavior (R = 0.4627; KD = 21.41%).Simultaneously, both significantly influenced learning behavior (F-count = 64.717 >F-table = 3.03). This study concludes that social media and online games, as partof students' digital reality, have a strong relationship with learning behavior inAqidah Akhlak (Islamic Creed) learning. Therefore, the use of digital technologyneeds to be directed wisely to support character-based and spiritual education.